Inverted Pendulum System - Nor Najihah, Awang (UTeM, 2008)
Inverted Pendulum System is a physical device consisting in a cylindrical bar which is usually made of aluminium, free to oscillate around a fixed pivot. The pivot is mounted on a cart, which can only moves in a horizontal direction. The cart can be exerted by a variable force. The bar would naturally tend to fall down from the top vertical position, which is a position of unsteady equilibrium. The goal of this project is to stabilize the inverted pendulum from falling down. This is possible by exerting on the cart through the motor a force which tends to contrast the 'free' pendulum dynamics. The correct force has to be calculated measuring the instant values of the horizontal position and the pendulum's angle. There is two controllers used and compared which are the PID controller and LQR controller. The modelling and analysis is done for both of these controllers in MA TLAB and Simulink. After that, the performances of these controllers are analyzed especially on the time taken to stabilize the pendulum and also the cart position. Therefore, the best control approach needs to be discovered in order to give the best performance for the inverted pendulum system.